Diagnostic Accuracy of Transabdominal Ultrasound (TAUS) in Detection of the Common Bile Duct Stone in Suspected Patients Taking Intra-Operative Findings as Gold Standard - Roshna Qamar, Muhammad Usman Farooq Baig, Rabia Ashraf, Tarab Kamran (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the diagnostic accuracy of transabdominal ultrasound (TAUS) in detection of the common bile duct stone in suspected patients taking intraoperative findings as gold standard. Method: This descriptive Cross-sectional Study was conducted in new radiology department, Services Hospital Lahore from February, 2018 till August, 2018. Data from 144 patients was calculated using non-Probability Consecutive sampling. Chi-square was used to explore the diagnostic accuracy of transabdominal ultrasound in detecting CBD among suspected patients. Results: the diagnosis accuracy of intraoperative surgery and TAUS for diagnosis of CBD, the results of Chi-square test revealed significant difference (X2=82.632, P=.000). The sensitivity was 82.69%, specificity was 92.39%, PPV was 86%, NPV was 90.43% and diagnostic accuracy of TAUS was 88.89%. Practical implication: "The study demonstrates the high diagnostic accuracy and practical benefits of transabdominal ultrasound (TAUS) as a non-invasive tool for detecting common bile duct stones, offering accessible and cost-effective diagnostic capabilities with no ionizing radiation or contrast material required." Conclusion: To concluded that the usage of TAUS as a tool for confirmation of presence of CBD stones at initial level is very valuable because of its numerous benefits such as easy accessibility, low in cost, no contrast material is required and ionizing radiation lacking. Hence, it is evident from the findings of current study that transabdominal ultrasound is a non-invasive technique devoid of complications as well as higher level of diagnostic accuracy in terms of detecting CBD stones. Keywords: Common bile duct stones, Transabdominal ultrasound, Diagnostic accuracy, Surgery